Churches of Moravian Serbia and the Main Directions of the Palaeologan Architecture - Maltseva, Svetlana V. (Actual Problems of Theory and History of Art, 2017)
The paper discusses the problematic issue of the relationship between the Serbian architecture ofthe so-called Morava school and other coeval trends in Byzantine architecture. In the second half of the 14th century the architecture of the Mediaeval Serbia enjoyed its last flourishing. Being originally one of the branches of the Byzantine architectural tradition, it became self-sufficient by that time. Serbian architecture continued to draw on Byzantine models in such issue as the typology of churches, the basic compositional principles, the general tendency towards a more decorative approach. On the other hand, its national peculiarity was also conspicuous.After the disintegration of the Empire of Uroš V, under the auspices of prince Lazar (1371–1389) and his noblemen a series of large churches were erected in Morava valley including Ravanica, Lazarica, Nova Pavlica, Veluce, Naupara and others. Almost all churches of this period are domed triconchs of two variants: either crossin-square or single-nave. The triconchs were known in Byzantine tradition from the Early Christian period and on, yet this typology was not wide-spread in the 14th century. The greatest part of the Morava valley triconchs are single-nave. In our opinion, this may be explained by the donors’ desire to be in keeping with the older Serbian tradition. Another specific trait is the tendency towards the vertical development of the composition. For this aim some particular constructions and decorative elements were used unfamiliar in Byzantine architecture. As for the decoration of the Morava valley churches, it is exclusively rich and diversified. Besides, the elements common in the Eastern Christian tradition, there are many others deriving from the West and introduced by the builders from the Adriatic littoral. The decoration of Morava valley churches is fully in keeping with the compositional logic and accentuates its predominating vertical development.
Keywords: Byzantine architecture; Palaeologan period; Serbian architecture; Morava school architecture